Hibridismo organizacional e sua interface com a performatividade crítica : estudo de caso em uma cooperativa de cafeicultores fair trade do Espírito Santo - Cezar, Layon Carlos (2018)
The objective of this thesis is to analyze the critical performativity engines present in a cooperative of Fair Trade coffee growers, verifying how they influence their hybrid condition. In order to respond to this research problem, an articulation betwee